SEKOLAH BERTARAF INTERNASIONAL - Tawil, Tawil (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2009)
International Standard School (ISS), is one of the primary and secondary education innovation in Indonesia, the main pillars for improved quality, relevance, and competitiveness. Stages that must be passed to become RSBI SBI, SSN, or SKM. This means to go to the ISS, the regular school must go through a phase of the SSN (the national standard of school) for elementary and junior high school, or SCA (School Category Autonomous) for secondary schools and vocational schools, and then increased to ISS (international standard school), and New to the ISS. ISS basically SSN plus. SSN for these schools, he said, still referring to the national standard schools by meeting the eight national education standards (NES), but must have a plus or international profits. Because ISS other than using the Indonesian language as the national language and the language of instruction in schools, ISS also require British language as the language of instruction in certain subjects, ISS also called school Bilangual Boarding School. Other things that must be met, such as the use of an international curriculum, international competence, qualifications of teachers and education staff is an international, English language acquisition for students, educators and educational staff at a particular level of a Toefl, culture and IT use (Information Technology), development of teaching strategies, use of facilities of international education, student exchanges with foreign countries ISS in OECD members, the exchange of educators with ISS overseas OECD members, management, financing, valuation, and international accreditation.